Pengaruh Likuiditas, Profitabilitas, Leverage dan Pertumbuhan Perusahaan Terhadap Kebijakan Dividen Perusahaan Manufaktur di BEI Pasca-Pandemi (2020-2023) - Totok Adhi Prasetyo; Anggun Anggun Citra; Oktavia Amanda P.; Rahmawati Rahmawati; Andi Supardi (Yayasan Miftahul Ulum Sangatta Kutai Timur (KEP. MENKUMHAM RI No. AHU-0014779.AH.01.04.Tahun 2018) bekerjasama dengan Jurusan Tarbiyah STAI Sangatta Kab. Kutai Timur., 2024)
This research aims to analyze the influence of liquidity, profitability, leverage and company growth on the dividend policy of manufacturing companies listed on the Indonesia Stock Exchange (BEI) in the 2020-2023 period. This research uses a non-participant observation method with a quantitative approach. This research focuses on 172 manufacturing companies as the research population. The research sample was selected using purposive sampling with the criteria of manufacturing companies listed on the IDX during the research period. with a sample of 10 companies. Secondary data in the form of financial reports was obtained from the official BEI website (idx.co.id). Data analysis uses multiple linear regression to test the influence of the independent variable on the dependent variable. It is hoped that this research can provide an empirical contribution regarding the factors that influence dividend policies of manufacturing companies in Indonesia in the post-pandemic context, as well as provide implications for investors, company management and capital market regulators. It can be concluded that traditional factors that are generally considered to influence dividend policy, such as liquidity, profitability, leverage, and company growth, do not provide an adequate explanation of the variation in dividend policy in the manufacturing companies studied.